Alternatives to the short-term The short term’s custodial sentence and its role in the rationalization of contemporary penal policy - Chouder, Amina; Zouache, Rabia (Journal of Human Sciences, 2021)
The short term’s custodial sentence has been widespread since its appearance in the eighteenth century,It was considered one of the most important punitive methods that helped to get rid of the harsh corporal punishment aimed at revenge on the perpetrator, However, the excessive implementation of this sanction led to the detection of its failure, given the negative effects of its application and that prevents achieving social reform and rehabilitation for prisoners ،so there was an urgent need to pursue a new punitive policy that relies on various punitive alternatives ،where these alternatives are resorted to whenever the circumstances of the crime and the character of the perpetrator. The comparative legislations have tended to include multiple and varied alternative penalties for the short term’s custodial sentence ,the algerian legislator also followed suit by adopting some of these alternatives as the last link of reform and rehabilitation.